Effect of repeated intraperitoneal injections of different concentrations of oxycodone on immune function in mice - Chen, Sumeng; Liu, Jingjing; Huang, Shaoqiang (Frontiers in Pharmacology, 2024)
Background: The effect of oxycodone as an opioid receptor agonist on immune function is still controversial. How oxycodone affects immune function as an opioid receptor agonist remains controversial. In this study, we investigated the possible effects of oxycodone on immune function in mice and its possible mechanisms of action. Methods: By repeated intraperitoneal injections of 25mg/kgmorphine,5mg/kg, 20mg/kg, 60mg/kg oxycodone, we assessed possible changes in the number of splenic lymphocytes and inflammatory cytokines within the serum of mice. CD4 + T cells and CD8 + T cells was sorted from spleen to observe whether the expression levels of opioid receptors and downstream signals were altered. Results: Repeated administration of oxycodone above 20 mg/kg resulted in significant weight loss. Repeated administration of oxycodone exhibits significant dose-dependent reduction in CD4 + T cells with little effect on CD8 + T cells, and little effect on inflammatory cytokine levels. Low-and Middle-dose oxycodone increased the mRNA expression level of MOR, KOR and DOR in different degree. Meanwhile, oxycodone increases mRNA expression levels of the TLR4 signaling pathway to varying degrees. Conclusion: Repeated intraperitoneal injection of oxycodone induces immunosuppression in mice.